Untangling the waterfall damsels: a review of the Mesoamerican genus Paraphlebia Selys in Hagen, 1861 (Odonata: Thaumatoneuridae) with descriptions of 11 new species - Ortega-Salas, Héctor; González-Soriano, Enrique; Jocque, Merlijn (Zootaxa, 2022)
A review of the Mesoamerican genus Paraphlebia Selys in Hagen, 1861 is presented, including diagnoses, illustrations of diagnostic characters, and distribution maps for all species. A key to the known males and females is provided. Eleven new species are described: P. akan Ortega-Salas & González-Soriano. sp. nov., P. chaak Ortega-Salas & González-Soriano sp. nov., P. chiarae Ortega-Salas sp. nov., P. esperanza Ortega-Salas & González-Soriano sp. nov., P. flinti Ortega-Salas & González-Soriano sp. nov., P. hunnal Ortega-Salas & González-Soriano sp. nov., P. itzamna Ortega-Salas, Jocque & González-Soriano sp. nov., P. ixchel Ortega-Salas & González-Soriano sp. nov., P. kauil Ortega-Salas & González-Soriano sp. nov., P. kinich Ortega-Salas & González-Soriano sp. nov., and P. kukulkan Jocque & Ortega-Salas sp. nov.